(untitled) (Journal of the College of Basic Education, 2022)
Montage is the backbone in the organic structure of the film’s achievement. Without it, we cannot realize the expressive elements of the film story, which without montage become scattered fragments that are not governed by controls or homogeneity among them, and we cannot call it in any way a stand-alone film without montage and in this regard. ((Malraux, Pudovkin and Eisenstein openly say that without editing, cinema would not be an art))().Montage may sometimes be called synthesis and at other times synthesis, but montage carries a large number of definitions, all of which are related to its importance and uniqueness in the specificity of expression.